JEJAK HISTORIS BENIH INJIL PERTAMA DI KEPULAUAN SIAU DAN RELEVANSINYA DALAM PERAYAAN HARI PEKABARAN INJIL - L M, Yusuf (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2025)
The first seed of the gospel sown by missionaries became the basis for establishing the celebration of the day of the proclamation of the gospel. This foundation is crucial for building the faith and spirit of gospel proclamation from generation to generation. A problem arises from the discrepancy between the age of the church as an institution and the age of the gospel proclamation day, which is celebrated annually in North Nusa, particularly on Siau Island. This has led to the misconception that the church as an institution was formed before the seeds of the gospel were sown. This study employs a descriptive qualitative method with a literature review approach, involving the collection of data and engagement with primary sources such as books, journal articles, and other relevant references related to the main topic of the research. The study concludes by tracing the historical path of the first gospel seeds in Siau. The findings indicate that the first seeds of the Gospel were sown by Pastor Mascarenhas in 1568 in the village of Paseng-Siau, which, by the most recent celebration in 2024, had reached an age of 456 years. Meanwhile, the age of Gospel proclamation that is commemorated annually, calculated from 1857 to 2024, spans 167 years. This period is categorized as a time of nurturing the Gospel seeds and enforcing strict church discipline. This long journey has made a significant contribution to establishing the historical foundation of Gospel ministry in the North Nusa region.